2021
DOI: 10.1111/ffe.13534
|View full text |Cite
|
Sign up to set email alerts
|

Influence of small defects and nonmetallic inclusions on the high and very high cycle fatigue strength of an ultrahigh‐strength steel

Abstract: The high and very high cycle fatigue (VHCF) properties of ultrahigh-strength Ck45M steel processed by thermomechanical rolling integrated direct quenching were investigated. S-N tests with smooth and small drilled holes containing specimens as well as near-threshold fatigue crack growth measurements were performed up to 2 Â 10 10 cycles using ultrasonic-fatigue testing technique. The fatigue strength of smooth specimens is mainly determined by the size of nonmetallic inclusions. For surface defects larger than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 66 publications
3
23
0
Order By: Relevance
“…Both KitalicIn for the CSR steel and KitalicdGBF for the CSR + VAR steel are about 5.0 MPa·m 0.5 , which is consistent with the previous research 8 . The high cycle (10 6 –10 7 ) and ultra‐high cycle (>10 7 ) fatigue tests of the SAE52100 steel show that the driving force motivating crack to propagate is about 5.0 MPa·m 0.5 regardless of high cycle or ultra‐high cycle tests 34,35 . This confirms that Kitalicth is the intrinsic characteristics of the steel and not affected by the stress amplitude and the fatigue cycle.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Both KitalicIn for the CSR steel and KitalicdGBF for the CSR + VAR steel are about 5.0 MPa·m 0.5 , which is consistent with the previous research 8 . The high cycle (10 6 –10 7 ) and ultra‐high cycle (>10 7 ) fatigue tests of the SAE52100 steel show that the driving force motivating crack to propagate is about 5.0 MPa·m 0.5 regardless of high cycle or ultra‐high cycle tests 34,35 . This confirms that Kitalicth is the intrinsic characteristics of the steel and not affected by the stress amplitude and the fatigue cycle.…”
Section: Discussionsupporting
confidence: 90%
“…8 The high cycle (10 6 -10 7 ) and ultra-high cycle (>10 7 ) fatigue tests of the SAE52100 steel show that the driving force motivating crack to propagate is about 5.0 MPaÁm 0.5 regardless of high cycle or ultra-high cycle tests. 34,35 This confirms that ΔK th is the intrinsic characteristics of the steel and not affected by the stress amplitude and the fatigue cycle. Due to this, for the RBF tests of the same material under the same stress amplitude, the crack size corresponding to ΔK th should be a constant.…”
Section: Inclusion Characterization and Fracture Topographysupporting
confidence: 66%
“…It can be seen that interior inclusions are smaller than √area = 125 µm for axial loading and √area = 196 µm for torsion loading can be considered as small cracks. Similar transition sizes between small and large defects (short and long cracks) are found for other high-strength steels [28,58].…”
Section: Discussionsupporting
confidence: 77%
“…The S-N curves exhibit clear knee points between 1 Â 10 5 and 2 Â 10 5 cycles. Only one specimen tested under fully reversed axial loading failed in the VHCF regime, which might be explained by environmental effects: The observability of nonpropagating cracks at small surface defects after testing at stress amplitudes below the fatigue limit, as demonstrated in a prior study 24 performed at R = À1, suggests that these arrested cracks can further grow after a sufficient number of load cycles in a chemically active F I G U R E 3 S-N diagrams for (A) uniaxial and (B) torsional test results at different load ratios(data obtained under uniaxial loading at R = À1 were already reported in Schönbauer et al 24 ) [Colour figure can be viewed at wileyonlinelibrary.com] environment (as ambient air for ultrahigh-strength steels). This effect is most pronounced at negative load ratios since nonpropagating cracks can be hardly observed at high tensile mean stresses (where once initiated cracks tend to further propagate until failure due to a lower contribution of crack closure).…”
Section: Specimens Containing a Small Drilled Holementioning
confidence: 78%
“…However, at fully reversed tensioncompression loading, failure from the surface was also observed in the VHCF regime (see Figure 3A). These data were evaluated in a previous study, 24 where it has been shown that fatigue failure occurred even at σ a /σ w = 0.73 from a small surface pit at N f = 6.48 Â 10 10 cycles. At positive load ratios, failure from surface inclusions and pits were not identified, which can be explained by the absence of nonpropagating cracks at stress amplitudes below the fatigue limit at high tensile mean stresses.…”
Section: Failure From the Surfacementioning
confidence: 99%